The effect of dimethyl sulfoxide (DMSO) on dentin bonding and nanoleakage of etch-and-rinse adhesives - Tjäderhane, Leo; Mehtälä, Pekka; Scaffa, Polliana; Vidal, Cristina; Pääkkönen, Virve; Breschi, Lorenzo; Hebling, Josimeri [UNESP]; Tay, Franklin R.; Nascimento, Fabio D.; Pashley, David H.; Carrilho, Marcela R. (Elsevier, 2013)
Objective The objective was to examine the effect of a solvent dimethyl sulfoxide (DMSO) on resin-dentin bond durability, as well as potential functional mechanisms behind the effect. Methods Microtensile bond strength (μTBS) was evaluated in extracted human teeth in two separate experiments. Dentin specimens were acid-etched and assigned to pre-treatment with 0.5 mM (0.004%) DMSO as additional primer for 30 s and to controls with water pre-treatment. Two-step etch-and-rinse adhesive (Scotchbond 1XT, 3M ESPE) was applied and resin composite build-ups were created. Specimens were immediately tested for μTBS or stored in artificial saliva for 6 and 12 months prior to testing. Additional immediate and 6-month specimens were examined for interfacial nanoleakage analysis under SEM. Matrix metalloproteinase (MMP) inhibition by DMSO was examined with gelatin zymography. Demineralized dentin disks were incubated in 100% DMSO to observe the optical clearing effect. Results The use of 0.5 mM DMSO had no effect on immediate bond strength or nanoleakage. In controls, μTBS decreased significantly after storage, but increased significantly in DMSO-treated group. The control group had significantly lower μTBS than DMSO-group after 6 and 12 months. DMSO also eliminated the increase in nanoleakage seen in controls. 5% and higher DMSO concentrations significantly inhibited the gelatinases. DMSO induced optical clearing effect demonstrating collagen dissociation. Significance DMSO as a solvent may be useful in improving the preservation of long-term dentin-adhesive bond strength. The effect may relate to dentinal enzyme inhibition or improved wetting of collagen by adhesives. The collagen dissociation required much higher DMSO concentrations than the 0.5 mM DMSO used for bonding. © 2013 Academy of Dental Materials.
Keywords: Dentin bonding; DMSO; Durability; Human; Long-term; Matrix metalloproteinase; Nanoleakage; Matrix metalloproteinases; Nanoleakages; Adhesives; Bond (masonry); Bond strength (materials); Collagen; Dimethyl sulfoxide; Dissociation; Enzyme inhibition; Resins; Water treatment; Organic solvents